2017
DOI: 10.1038/s41598-017-11717-9
|View full text |Cite
|
Sign up to set email alerts
|

Highly Effective Broad Spectrum Chimeric Larvicide That Targets Vector Mosquitoes Using a Lipophilic Protein

Abstract: Two mosquitocidal bacteria, Bacillus thuringiensis subsp. israelensis (Bti) and Lysinibacillus sphaericus (Ls) are the active ingredients of commercial larvicides used widely to control vector mosquitoes. Bti’s efficacy is due to synergistic interactions among four proteins, Cry4Aa, Cry4Ba, Cry11Aa, and Cyt1Aa, whereas Ls’s activity is caused by Bin, a heterodimer consisting of BinA, the toxin, and BinB, a midgut-binding protein. Cyt1Aa is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…We also show that the mixture of BinA subunit with Cyt1Aa was enough to induce toxicity in resistant larvae and for the internalization of BinA in the midgut cells. These data are consistent with the larvicidal activity previously recorded for a recombinant chimeric protein formed by BinA and Cyt1Aa against Bin-resistant C. quinquefasciatus and A. aegypti larvae (66). Our results indicate that BinA entry into the cytoplasm, which could be likely due to the pore formation of Cyt1Aa, is sufficient to provoke mortality and therefore to overcome the failures related to the BinB receptor-specific binding step (10,13,65,67).…”
Section: Discussionsupporting
confidence: 92%
“…We also show that the mixture of BinA subunit with Cyt1Aa was enough to induce toxicity in resistant larvae and for the internalization of BinA in the midgut cells. These data are consistent with the larvicidal activity previously recorded for a recombinant chimeric protein formed by BinA and Cyt1Aa against Bin-resistant C. quinquefasciatus and A. aegypti larvae (66). Our results indicate that BinA entry into the cytoplasm, which could be likely due to the pore formation of Cyt1Aa, is sufficient to provoke mortality and therefore to overcome the failures related to the BinB receptor-specific binding step (10,13,65,67).…”
Section: Discussionsupporting
confidence: 92%
“…Here we show, for the first time, that exchange of loops involved in insect specificity among toxins that are not related structurally is feasible and could provide tools for changing insect specificity and potentially for providing tools for countering resistance. A recent publication showed that Cyt1Aa-BinA hybrid toxins can be constructed resulting in hybrid-toxins with a broad-spectrum against mosquitoes including Anopheles gambiae, C. quinquefasciatus and A. aegypti 32 . These data indicate that Cyt1Aa toxin may accept larger domains and produce active proteins, suggesting that in the future other Cyt1Aa-hybrids could be constructed containing entire domains that could effectively enhance a lethal effect by Cyt1Aa in other targets.…”
Section: Discussionmentioning
confidence: 99%
“…Cyt1Aa, Cyt1Aa-hybrid, Cry11Aa, Cry1Ab or Cry1Ab-G439D protoxins were produced in B. thuringiensis 407 − acrystalliferous strain transformed with wild type or mutated plasmids. Plasmid pWF45 has cyt1Aa gene 32 or the new constructions of cyt1Aa-hybrid genes. Plasmid pCG6 contains cry11Aa gene 35 .…”
Section: Methodsmentioning
confidence: 99%
“…Of note, several of these recombinant/modified toxins have been introduced in genetically modified (GM) plants directly producing the toxins, thereby circumventing several limitations of topical insecticide applications (e.g., limited persistence, difficult timing of applications, and higher production costs) [ 53 ]. Cyt1Aa toxin from Bti has also been used to generate chimeras, expanding its host spectrum to other mosquito species when fused to the binary Tpp1Aa/2Aa (formerly BinAB) from Ls [ 74 ] and to lepidopteran when the recognition loop 3 of domain II from Cry1Ab was inserted between its loops 1 and 2 [ 75 ]. Interestingly, interdomains exchanges conducted between Cry11Aa and Cry11Ba from Bti and Btj , respectively, highlighted that while some domain combinations improved the mosquitocidal activity, others completely abolished the ability of the chimeras to form inclusions [ 76 , 77 ].…”
Section: Producing New Crystalline Toxins For the Development Of Innovative Bioinsecticidesmentioning
confidence: 99%
“…Moreover, the checkerboard-like crystal packing of Cry3Aa offers large solvent channels that could be able to accommodate a cargo protein up to ~50 Å in diameter ( Figure 3 ) [ 31 , 45 ]. This contrasts with other toxins, such as Cyt1Aa, which pack into crystals that might be too dense to allow a cargo protein to cocrystallize [ 88 ], although recent attempts suggest that it might not be an insuperable barrier [ 74 ].…”
Section: Functionalizing Toxin Crystals For the Development Of New Biotechnological Toolsmentioning
confidence: 99%